Sustainable Exploration of Biomass and Bioenergy Potential of Wetland Flora of Assam: a Conceptual Exposition - Hazarika, P.; Tripathi, Y. C. (Indian Forester, 2010)
Wetland ecosystem, the storehouse of renewable bio resources and biodiversity provides habitat and shelter to several plant, animal and microorganisms contributing significantly to the human livelihood and economy. People of Assam state have traditionally been utilizing these resources to fulfill their needs. However, wetlands of the state are under severe anthropogenic stress resulting into shrinkage of area and consequent loss of valuable resources and ecosystem as a whole warranting immediate conservation actions. The paper attempts to underline the concept of linking traditional knowledge with modern science and technology for sustainable bio resources utilization and biodiversity conservation of wetlands of Assam. Status and potential of wetland bio resource of Assam State for bio fertilizer and bio fuel production are discussed and appropriate agroforestry models are suggested for their conservation, management and productivity enhancement.